Vitamin E concentration in human milk and associated factors: a literature review - Mayara S.R. Lima; Roberto Dimenstein; Karla D.S. Ribeiro (Elsevier, 2014)
Objective: To systematize information about vitamin E concentration in human milk and the variables associated with this composition in order to find possible causes of deficiency, supporting strategies to prevent it in postpartum women and infants. Source: Studies published between 2004 and 2014 that assayed alpha-tocopherol in human milk of healthy women by high performance liquid chromatography were evaluated. The keywords used were "vitamin E", "alpha-tocopherol", "milk, human", "lactation", and equivalents in Portuguese, in the BIREME, CAPES, PubMed, SciELO, ISI Web of Knowledge, HighWire Press, Ingenta, and Brazilian Digital Library of Theses and Dissertations databases. Summary of the findings: Of the 41 publications found on the subject, 25 whose full text was available and met the inclusion criteria were selected. The alpha-tocopherol concentrations found in milk were similar in most populations studied. The variable phase of lactation was shown to influence vitamin E content in milk, which is reduced until the mature milk appears. Maternal variables parity, anthropometric nutritional status, socioeconomic status, and habitual dietary intake did not appear to affect the alpha-tocopherol levels in milk. However, the influence of the variables maternal age, gestational age, biochemical nutritional status in alpha-tocopherol, and maternal supplementation with vitamin E had conflicting results in the literature. Conclusion: Alpha-tocopherol concentration in milk decreases during lactation, until the mature milk appears. To confirm the influence of some maternal and child variables on milk vitamin E content, further studies with adequate design are needed. Resumo: Objetivo: Sistematizar informações sobre a concentração de vitamina E no leite humano e variáveis associadas a essa composição, a fim de encontrar possíveis causas de deficiência, subsidiando estratégias para prevenção desta em puérperas e lactentes. Fonte dos dados: Foram avaliados estudos publicados entre 2004 e 2014 que determinaram o alfa-tocoferol no leite humano de mulheres saudáveis por Cromatografia Líquida de Alta Eficiência. Os descritores utilizados foram "leite humano", "alfa-tocoferol", "vitamina E", "lactação" e seus equivalentes em inglês, nas bases de dados BIREME, Periódicos CAPES, PubMed, SciELO, ISI Web of Knowledge, HighWire Press, Ingenta e Biblioteca Digital Brasileira de Teses e Dissertações. Síntese dos dados: Das 41 publicações encontradas sobre a temática, 25 foram selecionadas, por possuirem texto completo disponível e se encaixarem nos critérios de inclusão. As concentrações encontradas de alfa-tocoferol no leite foram semelhantes na maioria das populações estudadas. A variável fase de lactação mostrou influenciar o conteúdo dessa vitamina no leite, que vai sendo reduzido até o leite maduro. As variáveis maternas paridade, estado nutricional antropométrico, condição socioeconômica e ingestão dietética habitual parecem não afetar os níveis de alfa-tocoferol no leite. Entretanto, a influência das variáveis idade materna, idade gestacional, estado nutricional bioquímico em alfa-tocoferol e suplementação materna com vitamina E possui resultados conflitantes na literatura. Conclusão: A concentração de alfa-tocoferol no leite diminui durante a lactação, até chegar ao leite maduro. Para confirmar a influência de algumas variáveis maternas e da criança sobre a vitamina E do leite ainda são necessários mais estudos, com desenho adequado. Keywords: Vitamin E, Alpha-tocopherol, Human milk, Lactation, Newborn, Palavras-chave: Vitamina E, Alfa-tocoferol, Leite humano, Lactação, Recém-nascido